Low cost microfluidic device for partial cell separation: micromilling approach - Lopes, Raquel (2015)
Several studies have already demonstrated that it is possible to perform blood flow studies in microfluidic systems fabricated by using low-cost techniques. However, most of these techniques do not produce microchannels smaller than 100 microns and as a result they have several limitations related to blood cell separation. Recently, manufacturers have been able to produce milling tools smaller than 100 microns, which consequently have promoted the ability of micromilling machines to fabricate microfluidic devices able to perform separation of red blood cells (RBCs) from plasma. In this work, we show the ability of a micromilling machine to manufacture microchannels with dimensions down to 30 microns. Additionally, we show for the first time the ability of the proposed microfluidic device to enhance the cell-free layer close to the walls, leading to perform partial separation of RBCs from plasma.